Donor Surfactant Protein D (SP‐D) Polymorphisms Are Associated With Lung Transplant Outcome. Issue 8 (10th July 2013) - Aramini, B.; Kim, C.; DiAngelo, S.; Petersen, E.; Lederer, D.J.; Shah, L.; Robbins, H.; Floros, J.; Arcasoy, S. M.; Sonett, J. R.; D'Ovidio, F.
Abstract: Chronic lung allograft dysfunction (CLAD) is the major factor limiting long‐term success of lung transplantation. Polymorphisms of surfactant protein D (SP‐D), an important molecule within lung innate immunity, have been associated with various lung diseases. We investigated the association between donor lung SP‐D polymorphisms and posttransplant CLAD and survival in 191 lung transplant recipients consecutively transplanted. Recipients were prospectively followed with routine pulmonary function tests. Donor DNA was assayed by pyrosequencing for SP‐D polymorphisms of two single‐nucleotide variations altering amino acids in the mature protein N‐terminal domain codon 11 (Met 11 Thr), and in codon 160 (Ala 160 Thr) of the C‐terminal domain. CLAD was diagnosed in 88/191 patients, and 60/191 patients have died. Recipients of allografts that expressed the homozygous Met 11 Met variant of aa11 had significantly greater freedom from CLAD development and better survival compared to those with the homozygous Thr 11 Th variant of aa11. No significant association was noted for SP‐D variants of aa160. Lung allografts with the SP‐D polymorphic variant Thr 11 Th of aa11 are associated with development of CLAD and reduced survival. The observed genetic differences of the donor lung, potentially with their effects on innate immunity, may influence the clinical outcomes after lung transplantation. Abstract : This study follows principles of Mendelian randomization to show that polymorphisms of the donor lung innate immunity molecule surfactant protein SP‐D predict recipient post—lung transplant development of chronic lung allograft dysfunction and survival.